Utilization of Natural Zeolite Catalyst Impregnated Sn Metal in Glucose Isomerization With Temperature Variations - Pamungkas, Dwi Putri W.; Amalia, Suci; Khalifah, Susi Nurul (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2015)
Studied the characteristics of natural zeolite catalysts activated and modifications and catalytic activity in the isomerization of glucose. Natural zeolite was activated by NH4NO3 2 M obtained catalyst HZA. While modification using 0,24 M Sn metal impregnated on HZA obtained catalyst Sn-HZA. At this stage, hydrothermal process carried out at temperature of 90 °C for 12 hours followed by calcination at temperature of 500 °C for 4 hours. The characterization includes the XRD analysis, SEM-EDAX analysis, acidity by ammonia method, and surface area by adsorption of methylene blue method. Glucose conversion was obtained through analysis of polarimeter at hour-0, 1, 2, 3, and 4 with temperature variation of 110, 120, and 130 °C. Solution which had the highest conversion resulted by polarimeter was analyzed by HPLC. XRD analysis showed that there were no changes in the structure of zeolite after activation and modification process. SEM-EDAX analysis showed that morphology of the zeolite surface is not damaged and Sn metal was successfully impregnated 6,94 %. The activity of HZA and Sn-HZA was 1,4850 mmol/g and 2,3145 mmol/g. while the surface area of HZA and Sn-HZA was 11,4077 m2/g and 11,4738 m2/g. Using the Sn-HZA catalyst with the reaction temperature of 120 °C provides the highest conversion of glucose and fructose selectivity. It were 14,0733 % w/v and 0,646 % w/v. Keywords: Catalyst, glucose, isomerization, natural zeolite, Sn metal.